KONSTRUKSI MASKULINITAS DALAM FILM MIRACLE IN CELL NO. 7 SERTA PEMANFATAANYA DALAM PEMBELAJARAN SASTRA - Wardani Putri, Thalia Aurora; Wicaksana, Muhlis Fajar; Septiari, Wahyu Dini (Universitas Negeri Makassar, 2024)
This research aims to describe the construction of masculinity in the main character in the Indonesian version of Miracle in Cell No. 7 and its utilization in literature learning. This research uses the descriptive-qualitative method; the data obtained is obtained through listening and note-taking techniques, then classified in the form of notes and documented in the form of screenshots. Data analysis in this research uses content analysis techniques. The results of this study reveal that the construction of masculinity in the Indonesian version of Miracle in Cell No. 7 is represented in an unusual form in general but still maintains its masculinity traits. The character Dodo Rozak has seven characteristics of masculinity, according to Chafetz, namely: male physical appearance; male functional; male sexual; emotional; intellectual; male interpersonal; and personal character. The characteristics of masculinity are used as an alternative teaching option in Indonesian language subjects at the high school level, especially in the context of learning literature, namely drama texts, specifically analyzing the content and language of dramas watched, in accordance with KD 3.19.